Examination of different grain hardness varieties of the grinding technology properties of wheat - P. Szabó, Balázs; Magyar, Zoltán; Véha, Antal (Acta Agraria Debreceniensis, 2018)
In the mill industry, the purpose of the grinding technology is to separate wheat endospermium and shell and to recover grists. The most important and the highest energy requirement operation is shredding. Flour quantity and quality produced from wheat depends on the variety of wheat that will be shredded, the type of grinding equipment and the condition used before the grinding. For this reason, during my experiments, I ground two grain structured varieties of wheat in laboratory conditions using a disk grinder, stone grinder and roll grinder in air-dry and conditioned states. We measured the equipment’s performance and the produced grist’s particle size distribution, followed by the calculation of the energy requirements of the grinders. In the grinding experiments we compared the ash contents of the different particle sized grist’s fractions to map the wheat’s particular properties.